A RUPELIAN CORAL REEF FISH ASSEMBLAGE FROM THE VENETIAN SOUTHERN ALPS (BERICI HILLS, NE ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
Here we describe a new bony fish assemblage collected from a fossiliferous outcrop located in Perarolo, Berici Hills, Venetian southern Alps. The fossiliferous deposits pertain to the Rupelian (lower Oligocene) Castelgomberto Calcarenite and are indicative of a tropical marine shallow water setting associated with coral reefs. The assemblage is characterized by diminutive putative cryptobenthic fishes, including a single goby (family Gobiidae) and several cardinalfishes of the subfamily Pseudmiinae (family Apogonidae. Furthermore, a new apogonine of the extinct tribe †Eoapogonini, a new butteflyfish (family Chaetodontidae), and an indeterminate viviparous brotula belonging to the ophidiiform family Dinematichthyidae, are also present, and likely represented part of the epibenthic community. Some of the taxa described herein are among the first occurrences for their respective lineages in the fossil record. The Perarolo taxa document the first Oligocene coral reef fish assemblage known to date. Four taxa are described as new: †Arconiapogon deangelii gen. et sp. n., †Chaetodon (Blumchaetodon) wattsi subgen. et sp. n., †Oligopseudamia iancurtisi gen. et sp. n., and †Oniketia akihitoi gen. et sp. n.
Keywords: Gobiidae; Apogonidae; Chaetodontidae; Dinematichthyidae; Oligocene; palaeoecology; Perarolo.